Independent Directors: An Indian Perspective - Tonk, Mohinder Singh (Prabandhan: Indian Journal of Management, 2012)
Board of Directors in a company comprises of the executive and non-executive directors. Executive directors are full-time employees of the company. They are responsible for managing the affairs of the company. However, given the day to day pressures, it can sometimes be extremely difficult for executive directors to remain independent and ensure necessary accountability. Non-executive directors, on the other hand, bring balance and credibility to the management decisions. The attributes of a non-executive director are independence of mind, integrity and the courage to question the executive members. Non-executive directors can add value to the Boards of companies of all size by ensuring transparency in the operations of a company, maintaining independent checks and balances on the authority of executive directors and CEO, bringing in specific skills and expertise, providing strategic vision, participating in the Audit and Nomination Committees and carrying out other responsibilities assigned to them from time to time. In order to objectively monitor organizational activities, non-executive directors must be independent. This implies that non-executive directors are not connected with the company or its promoters or directors on the basis of family relationship and do not have any other relationship, whether pecuniary or otherwise, with the company or its directors or related parties. To be able to effectively monitor, it is imperative that independent directors are given significant representation on the Board.